Design and analysis of a modular magnetically coupled quadratic boost topology with a damping network for DC microgrid - Ahmad A.; Singh R.K.; Mahanty R. (My University, 2025)
High voltage conversion ratio converter is required in broad range of applications such as microgrid, hybrid electrical vehicles, telecommunication and medical equipments. The control-to-output transfer function of a conventional quadratic boost converter reveals that right half plane (RHP) zero exist, which makes the controller design difficult. The device has to operate on extremely high duty cycle (to get high voltage conversion) and this leads to severe reverse recovery problem and increases EMI. In this paper, a modular magnetically coupled quadratic boost (MMCQB) topology with damping network for DC microgrid is proposed. The proposed topology consists of a magnetically coupled quadratic boost converter with damping network and a modular controller. In the proposed MMCQB converter the inductors of a quadratic boost converter are magnetically coupled and damping network is introduced. This arrangement facilitates complete elimination of RHP zero and thereby making it a minimum phase system unlike the conventional quadratic boost converter. This also facilitates simple controller design and better dynamic performance. The proposed MMCQB converter provides high step-up gain of 17-18 times. The proposed MMCQB topology is capable of accepting both DC and AC microsources. Detailed design and analysis of the MMCQB topology are carried out. Steady state and dynamic modeling are carried out to exhibit the advantages of the MMCQB topology. Finally, a prototype circuit is implemented to verify the performance of the proposed concept. © 2015 IEEE.